2021
DOI: 10.1371/journal.pone.0259352
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of industrial diversification and its determinants in West Germany: Evidence from population data of enterprises

Abstract: Germany is among the largest countries in the world in terms of total GDP, owing largely to rapid industrialization and expansion of economic activities into several sectors. This paper contributes to the literature on German economic development by investigating the evolution of industry diversification in Germany; particularly focusing on the recent concepts of related (RV) and unrelated variety (UV) in West German regions. It also identifies the statistical and economic determinants of variation in variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Individuals classified in the low economic status may not prioritize diet quality as healthier foods are more expensive; hence, they are more likely to purchase cheap food, high in fat and sugar, instead of buying foods high in fiber, which in turn translates into a lower diet quality [ 68 , 69 ]. Nevertheless, our results showed that adherence to the Mediterranean diet was lower among German participants, in line with the cultural differences in nutrition and eating behaviors, the German food being rich in energy and saturated fats and low in micronutrients [ 70 ]. These results, taken together, show that lower adherence to the Mediterranean diet does not necessarily mean a lower diet quality.…”
Section: Discussionmentioning
confidence: 79%
“…Individuals classified in the low economic status may not prioritize diet quality as healthier foods are more expensive; hence, they are more likely to purchase cheap food, high in fat and sugar, instead of buying foods high in fiber, which in turn translates into a lower diet quality [ 68 , 69 ]. Nevertheless, our results showed that adherence to the Mediterranean diet was lower among German participants, in line with the cultural differences in nutrition and eating behaviors, the German food being rich in energy and saturated fats and low in micronutrients [ 70 ]. These results, taken together, show that lower adherence to the Mediterranean diet does not necessarily mean a lower diet quality.…”
Section: Discussionmentioning
confidence: 79%
“…However, they did not find similar results for RV. In a recent study on the evolution of industrial variety in West Germany, Kublina and Ali (2021) found the sectoral shares to be less dominant than the entropy component in RV calculations. Their findings also reveal that in highly diversified regions, firm exits were more pronounced than the less diversified regions and regions diversify at the early stages of development; however, they switch to specialization after reaching a certain threshold level of development.…”
Section: Review Of Empirical Literaturementioning
confidence: 98%